Testing the influence of destination image and event quality on athletes' intentions to re-visit the city: a case study of the 2017 World youth and juniors' sambo championships in Novi Sad, Serbia. Issue 5 (2nd September 2020) - Matic, Radenko M.; Karagiorgos, Thomas; Maksimovic, Nebojsa; Alexandris, Kostas; Bujkovic, Rajko; Drid, Patrik
ABSTRACT: This study aimed to test the influence of destination image and event quality on athletes' intentions to repeat visiting the city in the future and develop positive word-of-mouth. Two hundred and twenty-five ( N = 225) questionnaires were collected, with an on-site survey, from athletes. Destination image was measured with the affective and cognitive dimensions (Kaplanidou & Vogt, 2007). Event quality was measured with three dimensions: core, tangibles and supporting (Alexandris, et al., 2017); finally, behavioural intentions were measured with intention to visit the city in the future and word-of-mouth communications (Alexandris, et al., 2017). The factorial validity of the scales was supported with a confirmatory factor analysis; the model showed acceptable fit indices: S-B χ 2 = 819.61, p < 0.001, NNFI = 0.95, CFI = 0.96, RMSEA = 0.08, RMSEA CI = 0.079–0.089. In terms of the intention to visit the city in the future, the results showed that the model predicted 21% of the variance ( F = 3.25, p < 0.001). All the dimensions had significant contributions to the prediction of intentions. In terms of the word-of-mouth communications, the model predicted 28% of the variance ( F = 4.04, p < 0.001). The tangibles and supporting dimensions had the most significant contributions. The theoretical and applied implications of these results are discussed.